Analytical Study on Interim Reporting and its Impact on Share Market Price - Dalvadi, Yagnesh M.; Raykundaliya, Dharmesh P. (Indian Journal of Finance, 2009)
The objective of interim reporting is to provide information to the stakeholders of the business to have an idea regarding capacity to generate earnings and cash flows, its financial condition and liquidity. Shareholder is real owner of the business. He is interested to know what the financial position of the business is and whether he should hold the shares of the company or to sell the shares? Interim reporting is very useful to them. If one can know the relation exits between interim repotting and its impact on share price, he can earn handsome amount of profit. In the present study an attempt is made to find out relation between interim reporting and its impact on share market prices.